A joint development of an e-learning management system with the IAEA: Transitioning from an on-premises hosting system to a cloud-based system - Kim, Hyeon-Jin; Kim, Kyoung-Pyo; Jeong, Ik (Edelweiss Applied Science and Technology, 2024)
The establishment of a Learning Management System (LMS) is a critical foundation for effective teaching and learning in virtual environments, enabling active participation by educators and learners. This study investigates the transition from self-hosted to cloud-based LMSs, focusing on a collaborative project between the Korea Atomic Energy Research Institute (KAERI) and the International Atomic Energy Agency (IAEA) initiated in late 2010. Using a three-step Focus Group Interview (FGI) process involving six experts in e-learning and human resource development (HRD), the study identifies latent elements and evaluates factors based on the Content Validity Ratio (CVR). Key findings highlight scalability, cost-effectiveness, integration with current systems, support for a variety of learning formats, and improved collaboration and communication, with a particular emphasis on supporting varied learning modalities and cost efficiency. The results indicate that cloud-based LMSs provide significant cost advantages for public institutions and meet the diverse educational needs of students. Cost reduction and adaptability to global enterprise collaboration emerge as crucial considerations for LMS adoption in public-sector settings.